A novel IMAC platform – adenosine coupled functional magnetic microspheres for phosphoproteome research. Issue 10 (21st February 2018) - Yan, Yinghua; Lu, Yujie; Chen, Mengying; Liang, Hongze
Abstract : Immobilized metal affinity chromatography is a powerful method for phosphopeptide enrichment. Abstract : Immobilized metal affinity chromatography is a powerful method for phosphopeptide enrichment. However, the achievement of highly specific enrichment and sensitive detection of phosphopeptides by this method remains a big challenge due to the lack of high specificity and large binding capacity of conventional materials. In this work, adenosine tri-phosphate modified hydrophilic Fe3 O4 @PDA core–shell microspheres with Ti 4+ exterior walls were successfully synthesized through a facile reaction at room temperature. The thicker grafting layer of the dopamine decoration exhibited enhanced hydrophilicity and biocompatibility, and the adenosine tri-phosphate molecule could offer superiorly strong and active metal phosphonate sites to bind phosphopeptides. The prepared microspheres demonstrated a low limit of detection (2 fmol), along with an exceptionally great specificity to capture phosphopeptides from a tryptic digest of the mixture of a nonphosphorylated protein BSA and a phosphorylated protein β-casein with molar ratios of BSA/β-casein up to 1000 : 1, and phosphopeptides from human serum and defatted milk were captured with high sensitivity and selectivity. In addition, the high magnetic susceptibility allowed convenient separation of the target peptides by magnetic separation. These outstanding features give the Ti 4+ -adenosine tri-phosphate-Fe3 O4 @polydopamine microspheres many advantages for mass spectrometric analysis of phosphopeptides.